Development and validation of the Japanese version of the problem gambling severity index. (November 2019) - So, Ryuhei; Matsushita, Sachio; Kishimoto, Sanae; Furukawa, Toshi A.
Abstract: Background: The Problem Gambling Severity Index (PGSI) has been the most frequently used instrument for prevalence studies of problem gambling in the 2010s. However, the Japanese version of the PGSI has yet to be developed. Objective: To develop the Japanese version of the PGSI and to investigate its reliability and validity. Materials and methods: We translated and back-translated the original version of the PGSI into Japanese. The author of the original PGSI confirmed the semantic equivalence between the original PGSI and its Japanese version. We examined the reliability and validity of the Japanese version of the PGSI using data from a nationwide prevalence study of problem gambling conducted in Japan in 2017. Results: Usable responses were obtained from 5365 residents. The PGSI had excellent internal consistency (Cronbach's alpha coefficient: 0.89) and moderate test-retest reliability after 45–60 days (intraclass coefficient: 0.54). Exploratory factor analysis revealed the unidimensionality of the PGSI. As for criterion validity, using the diagnosis of gambling disorder in DSM-5 as a reference standard, the stratum specific likelihood ratios of the PGSI score of 0 = non-problem; 1–2 = low risk; 3–7 = moderate risk; and 8–27 = problem gambling were 0.00; 0.68 (95% confidence interval: 0.21 to 2.22); 8.71 (5.2 to 14.5); and 67.9 (35.6 to 129.5) respectively. Conclusions: We recommend including the PGSI in future prevalence studies of problem gambling in Japan. Highlights: A validation study of the Japanese version of the problem gambling severity index (PGSI) in a nationwide community sample. The Japanese version of PGSI had excellent internal consistency and moderate test-retest reliability. We demonstrated the PGSI had good criterion validity using the diagnosis of gambling disorder in DSM-5 as a reference standard.